2022
DOI: 10.1007/s10209-022-00931-6
|View full text |Cite
|
Sign up to set email alerts
|

Does the law matter? An empirical study on the accessibility of Finnish higher education institutions’ web pages

Abstract: Information and communication technology (ICT) has made higher education available to many students in a new way. The role of online learning in higher education institutions (HEIs) has grown to an unprecedented scale due to the COVID-19 pandemic. The diversity of higher education students has increased, and accessible solutions are needed. New European and national regulations support these trends. The research reported in this paper was conducted in Finland, which is one of the leading European countries in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Laamanen et al [11] tested 38 homepages of Finnish universities by using WAVE and Siteimprove accessibility checking tools. The results showed low accessibility, with an average of 65 errors per institution detected with WAVE, with a maximum of 1 and a maximum of 704.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Laamanen et al [11] tested 38 homepages of Finnish universities by using WAVE and Siteimprove accessibility checking tools. The results showed low accessibility, with an average of 65 errors per institution detected with WAVE, with a maximum of 1 and a maximum of 704.…”
Section: Related Workmentioning
confidence: 99%
“…The results are presented in Table 1. The most frequent errors on the home page are related to the use of tags vs. CSS (64), text describing link purpose (24), text alternative (11), and table issues (10). The most frequent errors on the admission page are related to the text describing link purpose (21), improper heading ordering (14), and use of tags vs. CSS (5).…”
Section: University Of Bucharest (Ub)mentioning
confidence: 99%
“…The motivation to do this research came from the fact that my home organization, Laurea University of Applied Sciences, is currently developing a new online store which also must meet EU-level accessibility standards. The state of accessibility of the websites of Universities of Applied Sciences and universities has been studied before [2,9], but e-commerce has been outside the scope of those studies. In part, this is due to the fact that Universities of Applied Sciences selling educational services online is a relatively new phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research studies (Loiacono and Djamasbi, 2013;Stuy, 2018) have examined the influence of legislation on corporate decision to provide an accessible website and concluded that there is significant need for legislative amendments for enhanced corporate compliance. A survey of 8057 municipal websites ten years after the enactment of the Stanca Act in Italy, revealed that most websites are not accessible, some failing even very basic tests of accessibility (Barricelli et al, 2018)., Laamanen, et al (2022)'s study of Finnish higher education institutions' web pages using accessibility checkers revealed an average number of 119 errors per institution (minimum 3 and maximum 1165), despite the European Union's various policies and initiatives aimed at establishing an equal society and Finland's Act 306 of 2019 on the Provision of Digital Services. Motivated by these studies, we pose two research questions.…”
Section: Introductionmentioning
confidence: 99%